Quality Control of Knitting Process with 4QC Tools and Failure Mode and Effect Analysis (FMEA) - Dwi Adi Sucipto; Dene Herwanto (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
PT. Radian Putra Metropolindo Pratama is a company that manufactures military and non-military accessories. This research is based on not yet optimal of quality control application in the knitting process and high percentage of NG. The solution method used is a tool 4QC, including check sheet, scatter diagram, control chart, fishbone diagram and FMEA. Based on production data for the period September to October 2021 the number of NG grey in the process of knitting reach of 2.01%. Improvement analysis is performed to see other potential failures using FMEA with severity, occurrence and detection value calculations. The results of the weighting RPN identify three potential failure high, that the defect needle, broken needle, and closed needle, each of 108, 144, and 144. Recommended actions given, including periodic inspection of component materials, repair of storage systems, making schedules of maintenance and repair of components, update of knitting SOP, and operator training. PT. Radian Putra Metropolindo Pratama adalah perusahaan yang memproduksi aksesoris militer dan non militer. Penelitian ini didasari oleh belum optimalnya penerapan pengendalian kualitas pada proses rajut dan tingginya persentase NG. Metode penyelesaian yang digunakan adalah 4QC Tools, diantaranya lembar periksa, diagram sebar, peta kendali, diagram tulang ikan dan FMEA. berdasarkan data produksi periode September sampai Oktober 2021 jumlah grey NG pada proses rajut mencapai 2,01%. Analisis perbaikan dilakukan menggunakan FMEA dengan perhitungan nilai severity, occurrence dan detection. Hasil pembobotan RPN mengidentifikasi tiga potensi kegagalan tertinggi, yaitu jarum rusak, jarum patah, dan jarum menutup, masing-masing sebesar 108, 144, dan 144. Rekomendasi tindakan yang diberikan, diantaranya pengecekan berkala bahan komponen, perbaikan sistem penyimpanan, membuat jadwal perawatan dan perbaikan komponen, pembaruan SOP rajut, dan pelatihan operator.